Plan de desarrollo turístico para la comunidad de la Chimba, Cantón Cayambe, Provincia de Pichincha. - Andrango Nepas, Jessica Angelica (2015)
The community of “ la Chimba”, is located in the parish of Olmedo, an hour from the canton of Cayambe, Pichincha province, with a population dedicated to livestock and agriculture, is a strategic place to propose tourist alternatives, from it is the entry point in the reserve Cayambe-Coca, also has a historical relevance of national importance of this community is buried the remains of a large indigenous leader Tránsito Amaguaña that fight for the rights to education, to the lands of the peasants. This so-called research: tourism for the Chimba community development plan, aims to contribute to its economic improvement considering tourist activities that generate additional economic activity, allowing the use of suitable existing natural and cultural wealth, improving the quality of life of its habitants, post the tourism has come to position itself as one of the fastest growing in the world socio economic activities which promotes economic development and alleviate poverty. This document is made based on the previous diagnosis, where determined activities that directly relate to tourism as a generator of jobs, among which are: the determination of a tourist product, approach to training programs, strengthening the identity, signage, improvement of admission to the attractions and finally, a draft advertising to publicize the attractions and tourist services are there in the community. The development of research, applied quantitative, same methodology allowing to collect data and information directly from the residents of the community and the quantitative to delve into the calculations and descriptive data that meet the specific needs of those involved.